A dinâmica agrária recorrente da soja e da silvicultura na fronteira Livramento/BR e Rivera/UY e seus impactos na agricultura familiar: 2006-2016 - Netto, Tatiane Almeida (2017)
In the border of Livramento/BR and Rivera/UY we identified the territorialization of forestry and soybean, resulting from the modification of the agricultural productive system, driven by trade agreements and the link to foreign capital. By identifying the progress of these productive systems in the last decade, we observe the reorganization of space, the forms of work associated with these crops, and the introduction of new social relations with the transformation of its productive arrangement influenced by the approach of agrarian capitalism that transforms space by inserting new social agents in dispute in the territory. According to the concept of territory, this thesis analyzes the development of agrarian capitalism in the border and the impacts of the soybean chain and forestry in family farming. In order to understand the different territorializations in the spaces studied, with special emphasis on family farming, we carried out a research based on elements of bibliographic research, documentary research, prioritizing the secondary data: Census of the Brazilian Institute of Geography and Statistics (IBGE), Uruguay 2011 Census, National Statistical Institute (INE), Agricultural Census 2011, Agricultural Statistics (DIEA) linked to the Ministry of Livestock, Agriculture and Fisheries (MGAP). We also carried out field research, characterized by direct observation, whose records are in a field diary, as well as the formulation of instruments, with special emphasis on questionnaires and interviews applied to producers, technicians and public authorities in order to understand the transformations carried out in that border in the last decade, with the consequent territorial reconfiguration of the rural space, notable for the implantation of forestry and soybean culture, minimizing the historical participation of livestock production in that region, a phenomenon that occurs both in the area occupied by family farming and in the areas occupied by large enterprises. Family farmers are adapting to remain active, relating to the soybean and forestry chains by adopting new strategies of social reproduction and at the same time disputing the territory with the mentioned chains. Among the strategies adopted are: multifunctionality, pluriactivity, investments in agroecological models of production, women’s empowerment in the countryside, diversity in agricultural production and technology inversion.